THE PRELIMINARY STUDY ON IMPLEMENTING A SIMPLIFIED SOURCE TERMS ESTIMATION PROGRAM FOR EARLY RADIOLOGICAL CONSEQUENCES ANALYSIS - Theo Alvin Ryanto; Jupiter Sitorus Pane; Muhammad Budi Setiawan; Ihda Husnayani; Anik Purwaningsih; Hendro Tjahjono (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
Indonesia possesses numerous potential sites for nuclear power plant development. A fast and comprehensive radiological consequences analysis is required to conduct a preliminary analysis of radionuclide release into the atmosphere, including source terms estimation. One simplified method for such estimation is the use of the Relative Volatility approach by Kess and Booth, published in IAEA TECDOC 1127. The objective of this study was to evaluate the use of a simple and comprehensive tool for estimating the source terms of planned nuclear power plants to facilitate the analysis of radiological consequences during site evaluation. Input parameters for the estimation include fuel burn-up, blow-down time, specific heat transfer of fuel to cladding, and coolant debit, using 100 MWe PWR as a case study. The results indicate a slight difference in the calculated release fraction compared to previous calculations, indicating a need to modifyÂ Keywords:Â Source terms, Relative volatility, Release fraction, PWR, SMART